Evaluation of health care and husbandry system of calves at buffalo farms in southern Bangladesh (SAARC Journal of Agriculture, 2016)
Calves with optimum health play a crucial role for sustainability of the dairy farms. This study was conducted to evaluate the present status of calf health care and husbandry system on 140 buffalo farms in southern Bangladesh. The data were collected during farm visit and recorded in prepared questionnaire. The results of the present study revealed that significantly lower number of farms (15.0%) had calves with good body condition (p